Qu’est-ce qu’une techno-image ? - Vincent Jacques (Appareil)
This article examines the question of Flusser’s technical determinism. In order to understand the nature of this determinism, the concepts of technical image (techno-image) and apparatus will be analyzed in detail. By tracing the passage from the age of machines to the age of apparatus, we will see the relation that the philosopher poses between technical development and relationship to the world. We will thus try to define what it means to live in a system of organization in network of the apparatus. An existential question, which touches as well on our mode of collective being as on the meaning of knowledge produced more and more automatically by the techno-science of today. As a response to the threats of an automated technical world, the philosopher develops the concept of technical imagination, whose implications will finally be analyzed.